Approval and Withdrawal of New Antibiotics and Other Antiinfectives in the U.S., 1980–2009. Issue 3 (1st October 2013) - Outterson, Kevin; Powers, John H.; Seoane‐Vazquez, Enrique; Rodriguez‐Monguio, Rosa; Kesselheim, Aaron S.
<x xml:space="preserve">Abstract</x> Numerous reports have noted decreasing numbers of antibiotic approvals. To determine the context for this decline, we examined all new molecule entities (NMEs) and new biologic licenses (NBLs) approved by the FDA from 1980–2009, and compared approval rates of the 61 approved antibiotics to trends in other drug classes. We also tracked withdrawals of approved drugs and found more withdrawals for antibiotics than other drug classes. After adjusting for drugs subsequently withdrawn, the record for antibiotic innovation is less dire than previously reported. We also report problems with the quality of the approved antibiotics studied. Future policies providing incentives for new antibiotic development should not be based on simple numerical targets and key provisions should ensure appropriate quality as well as quantity of antibiotic drug innovation.